PESAN DAKWAH DALAM TRADISI MACOPAT DI DUSUN MORALAS DESA KARDULUK KECAMATAN PRAGAAN - Uswatun Hasanah (Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
Da'wah is one of the processes of the entry of Islam into Indonesia through culture, so the entry of Islam into Indonesia is quite short because the surrounding community is already attached to the local culture, so that the entry of Islam is subtle without going through violence, because Islam itself respects the pluralism of a society. Human relations with da'wah also study about humans and all the culture they have, humans are social beings while da'wah is the object. One example of da'wah combined with culture by Wali Songo is the Durma song